2021
DOI: 10.1007/s42764-021-00046-x
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 is a deacetylase of N4-acetylcytidine on ribosomal RNA

Abstract: N-acetyltransferase 10 catalyzes RNA N4-acetylcytidine (ac4C) modifications and thus regulates RNA stability and translation efficiency. However, the deacetylase for ac4C is unknown. SIRT7 was initially identified as an NAD+-dependent protein deacetylase and plays essential roles in genome stability, circadian rhythms, metabolism, and aging. In this study, we identified SIRT7 as a deacetylase of the ac4C of ribosomal (r)RNA for the first time and found it to be NAD+-independent. Our data highlight the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Recently, ac 4 C has been described as the sole acetylation event in eukaryotic RNA at a level of ~1 ac 4 C residue per mRNA on cellular mRNAs 4 . Different from m 6 A modification, only one ac 4 C eraser (SIRT7) but no reader has been found so far 32 , while NAT10 has been identified as the only known acetyltransferase in human RNAs, which catalyzes ac 4 C deposition on different RNA substrates with acetyl-CoA serving as the acetyl donor 2 , 33 . In the case of cellular mRNAs, Arango et al utilized transcriptome-wide approaches to investigate ac 4 C localization and function in mRNA and discovered that ac 4 C catalyzed by NAT10 within target mRNAs conferred enhanced stability and translation efficiency 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ac 4 C has been described as the sole acetylation event in eukaryotic RNA at a level of ~1 ac 4 C residue per mRNA on cellular mRNAs 4 . Different from m 6 A modification, only one ac 4 C eraser (SIRT7) but no reader has been found so far 32 , while NAT10 has been identified as the only known acetyltransferase in human RNAs, which catalyzes ac 4 C deposition on different RNA substrates with acetyl-CoA serving as the acetyl donor 2 , 33 . In the case of cellular mRNAs, Arango et al utilized transcriptome-wide approaches to investigate ac 4 C localization and function in mRNA and discovered that ac 4 C catalyzed by NAT10 within target mRNAs conferred enhanced stability and translation efficiency 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we failed to detect interaction between p65 and NAT10, suggesting a less possibility of NAT10 directly acetylating p65. We assume an existence of some indirect mechanisms, for instances, through SIRT1 and SIRT7, two NAD-dependent deacetylases which are reported to form complex with NAT10 10,13 , by which NAT10 might affect the activity of nuclear p65. As previously reported, SIRT1 S-nitrosylationdependent acetylation of p65 contributes to muscle wasting in burn wound repair; and SIRT7 regulating p65 is involved in in ammation process, and TGF-β signaling transduction in the tissue repair process 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibiting NAT10 extended the healthy lifespan in an Lmna G609G progeria mouse model, suggesting its intimate link with aging 11 . Recent ndings revealed that N 4 acetylcytidine (ac4C) modi cation of tRNA, rRNA, and mRNA is catalyzed by NAT10, improving the stability of RNA and protein translation e ciency 12,13 . For example, NAT10 has been found to execute ac4C acetylation for mRNA of RUNX2 and COL5A1, which prevents ovariectomy-induced bone loss and promotes gastric cancer metastasis, respectively 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we failed to detect interaction between p65 and NAT10, suggesting a less possibility of NAT10 directly acetylating p65. We assume an existence of some indirect mechanisms, for instances, through SIRT1 and SIRT7, two NAD-dependent deacetylases which are reported to form complex with NAT10 [10,13], by which NAT10 might affect the activity of nuclear p65. As previously reported, SIRT1 S-nitrosylation-dependent acetylation of p65 contributes to muscle wasting in burn wound repair; and SIRT7 regulating p65 is involved in inflammation process, and TGFβ signaling transduction in the tissue repair process [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibiting NAT10 extended the healthy lifespan in an Lmna G609G progeria mouse model, suggesting its intimate link with aging [11]. Recent findings revealed that N 4 -acetylcytidine (ac4C) modification of tRNA, rRNA, and mRNA is catalyzed by NAT10, improving the stability of RNA and protein translation efficiency [12,13]. For example, NAT10 has been found to execute ac4C acetylation for mRNA of RUNX2 and COL5A1, which prevents ovariectomy-induced bone loss and promotes gastric cancer metastasis, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%